Structural and spectroscopic investigations of nine-coordinate redox active lanthanide complexes with a pincer O, N, O ligand. Issue 24 (8th June 2020) - Mouchel Dit Leguerrier, D.; Barré, R.; Bryden, M.; Imbert, D.; Philouze, C.; Jarjayes, O.; Luneau, D.; Molloy, J. K.; Thomas, F.
Abstract : Three ligand molecules coordinate under their anionic diamagnetic form; the complexes (Gd, Eu, Yb, Lu) can undergo reversible oxidations, affording radical species, as demonstrated by spectro-electrochemistry. Abstract : The lanthanide complexes EuL3, GdL3, YbL3 and LuL3 of the N, N ′-bis(2-hydroxy-di-3, 5- tert -butylphenyl)amine were prepared. The X-Ray crystal structures of GdL3 and LuL3 demonstrated a nine-coordinate sphere with three ligand molecules under their anionic diamagnetic form (Cat-N-BQ) − . The complexes showed three oxidation events ( E ox11/2 = 0.15–0.16 V, E 1/2 2 = 0.51–55 V, and E 1/2 3 = 0.75–0.78 V vs. Fc + /Fc) via cyclic voltammetry, corresponding to the successive oxidation of the aminophenolate moeities to iminosemiquinone species. The complexes GdL3 and YbL3 were characterized by EPR spectroscopy, allowing for the determination of the zero field splitting (ZFS) parameters in the first case. The monocations (LnL3 ) + and monoanions (LnL3 ) − were electrochemically generated (Ln = Eu, Gd, Yb, Lu), as well as the dications YbL3 2+ and LuL3 2+ . The spins are antiferromagnetically exchange coupled in the diradical species LuL3 2+ (| D | = 260 MHz, E = 0). All the complexes (incl. neutral) possess a strong absorption band in the NIR region (730–840 nm, ε > 19 mM −1 cm −1 ) corresponding to ligand-based transitions.